Electric drive of locomotive motor-fans development - Ivanov, Stanislav (National Technical University "Kharkiv Polytechnic Institute", 2024)
The circuit and technical solutions used in the creation of the electric drive of motor-fans for cooling locomotive equipment have been analyzed. It has been established that the frequency-controlled electric drive based on asynchronous electric motors prevails on modern locomotives. This allows adjusting the performance of the fans depending on the equipment load. The application of synchronous-reactive electric motors, which have increased energy characteristics, in frequency-controlled electric drives is proposed.
Keywords: asynchronous electric motors; fans motors; energy efficiency; locomotives; electric drive